«Léxico Mayor de Cuba»: notes on usage labels in an author's dictionary (Islas, 2023)
Introduction: This article is dedicated to the study of usage labels in the Léxico Mayor de Cuba. It aims to provide a conceptual approach to the phenomenon and analyze its treatment in an author's dictionary.Methods: A sample of 26 words from the dictionary was used, employing the method of structured observation, which allows for the use of a set of conceptual guidelines to organize the analysis.Results: The study provides an inventory of the marking system followed by the author and summarizes the information that can be obtained through it.Conclusions: The analyses conducted lead to the conclusion that, although there is no defined marking system in the dictionary, it is possible to obtain characteristics of word usage restrictions and conditions, as well as insights into the author's identity and ideology.
Keywords: author's lexicography; usage marks; ideology